Automatic Segmentation of Abdominal Aortic Aneurism (AAA) By Using Active Contour Models - Kosasih, Rifki (Universitas Negeri Semarang, 2020)
Abdominal aortic aneurysm (AAA) is a disease that is caused by dilation of the aortic wall. Dilation of the aortic wall will affect the size of the diameter of lumen and the aorta. In this study we use T1 and T2 images on 4 patients with AAA which generated from MR Imaging to calculate the diameter of the abdominal aortic aneurysm (AAA). To calculate the diameter of lumen and the aorta, the first step is image registration using Laplacian eigenmap method. After that we propose an automatic segmentation method on region of the aorta by using active contour models to get the contour of lumen and the aorta. The last step, Â we calculate the diameter of lumen and the aorta by using contour of lumen and the aorta. In our experiment, active contour model is very good method for segmentation AAA. In the result, our proposed model give the accuracy rate of lumen is 96.41% and accuracy rate of aorta is 95.22%.Â